The Influence of The Use of Animation Media on The Results of Students in Kalor Transfer Materials - Elma Zurika; Soewarno; Muhammad Daud (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2020)
Student learning outcomes are still low in physics, especially heat transfer material, this is because educators do not use learning media when the teaching and learning process takes place, thus making students feel bored and bored. One solution that can overcome these problems is to use animation media. This study aims to determine the effect of the use of animation media on student learning outcomes. The method used in this study was Quasi Experiment with Pretest-posttest Experimental Control Group Design, which involved the experimental class X IPA1 of 24 students and the control class X IPA2 of 24 students. Data collection was carried out with multiple-choice test questions. The test result data were analyzed using the t-test formula. Based on the results of calculations from statistical tests show that the t-test is table is 14.31> 1.67 for a significant level of 95% or ⍺ = 0.05 so that the hypothesis Ho is rejected and Ha is accepted. The results of this study indicate that there is a positive influence on the use of animation media on learning outcomes of students in class X MAN Darussalam Aceh Besar on the heat transfer material. This can be seen with the learning outcomes of students in the experimental class 82.87.